A suitable scheme of dynamic initialization for a multi-level primitive equations model in tropics (MAUSAM, 1988)
A number of numerical experiments are carried out to find a suitable dynamic initialization scheme for tropics. The experiments are carried out with a multi-level primitive equations model with sigma as the vertical coordinate. The performance of different initialization schemes are evaluated from the initialized 12 and 24 hours forecast fields. It is found that all the different types of dynamic initialization yield almost, similar results. However, on the basis of the overall performance and computational economy considerations, the Okamura scheme is preferred.